Differential effect of assisted reproductive technology and small‐for‐gestational age on fetal cardiac remodeling. (July 2017) - Valenzuela‐Alcaraz, B.; Crispi, F.; Cruz‐Lemini, M.; Bijnens, B.; García‐Otero, L.; Sitges, M.; Balasch, J.; Gratacós, E.
ABSTRACT: Objective: Fetuses conceived by assisted reproductive technology (ART) and those that are small‐for‐gestational age (SGA) show cardiovascular remodeling in utero ; however, these two conditions are often associated. We aimed to evaluate the differential effect of ART and SGA on fetal cardiac remodeling. Methods: This was a prospective cohort study of term singleton pregnancies seen at our department between April 2011 and September 2013. The cohort was divided according to fetal growth and mode of conception into the following four groups: 102 appropriate‐for‐gestational‐age (AGA) fetuses conceived spontaneously (controls), 72 AGA fetuses conceived by ART (ART‐AGA), 31 SGA fetuses conceived by ART (ART‐SGA) and 28 SGA fetuses conceived naturally (Spont‐SGA). SGA was defined as birth weight < 10 th centile. Fetal echocardiography was performed at 28–32 weeks to assess cardiac dimensions, geometry and function. Results: ART fetuses had dilated atria (mean left atrium‐to‐heart area ratio: controls, 15 ± 2.7%; ART‐AGA, 18 ± 4.1%; Spont‐SGA, 14 ± 3.7%) and more globular ventricles (left ventricular sphericity index: controls, 1.77 ± 0.2; ART‐AGA, 1.68 ± 0.2; Spont‐SGA, 1.72 ± 0.2), with normally sized hearts. In contrast, SGA fetuses had enlarged hearts (cardiothoracic ratio: controls, 24 ± 3%; ART‐AGA, 24 ± 4%; Spont‐SGA, 29 ± 6%), preserved atrial size, more globular and concentric hypertrophic ventricles (left ventricle relative wall thickness: controls, 0.48 ± 0.17; ART‐AGA, 0.54 ± 0.13; Spont‐SGA, 0.63 ± 0.23). Both ART and SGA fetuses had decreased longitudinal motion (tricuspid annular ring displacement: controls, 6.5 ± 0.8 mm; ART‐AGA, 5.5 ± 0.7 mm; Spont‐SGA, 5.9 ± 0.6 mm) and impaired relaxation (left isovolumetric relaxation time: controls, 47.0 ± 7.3 ms; ART‐AGA, 50.0 ± 7.9 ms; Spont‐SGA, 49.5 ± 9.3 ms). ART‐SGA fetuses presented a combination of features from both ART and SGA groups. Conclusion: SGA and conception with ART were associated with distinct patterns of fetal cardiac remodeling, supporting the concept that they are independent causes of cardiac programming. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 50: 17–18